Design study of composite repair system for offshore riser applications - Chan, Park Hinn (2017)
Risers in offshore operations are subjected to corrosion during their service life cycle. The use of relatively inexpensive, high strength to weight ratio fibre reinforced polymer composite (FRPC) as a load bearing pipe repair sleeve is an emerging technology that is becoming common for offshore applications. Risers experience complex loading profiles and experimental investigations often incur substantial time, complicated instrumentation and setup costs.